Dolphin CONTINUE: a multi-center randomized controlled trial to assess the effect of a nutritional intervention on brain development and long-term outcome in infants born before 30 weeks of gestation - E. Janson; P. C. M. P. Koolschijn; L. Schipper; T. D. Boerma; F. N. K. Wijnen; W. P. de Boode; C. H. P. van den Akker; R. G. Licht-van der Stap; D. H. G. M. Nuytemans; W. Onland; S. A. Obermann-Borst; J. Dudink; et al. (BMC, 2024)
Abstract Background Preterm born infants are at risk for brain injury and subsequent developmental delay. Treatment options are limited, but optimizing postnatal nutrition may improve brain- and neurodevelopment in these infants. In pre-clinical animal models, combined supplementation of docosahexaenoic acid (DHA), choline, and uridine-5-monophosphate (UMP) have shown to support neuronal membrane formation. In two randomized controlled pilot trials, supplementation with the investigational product was associated with clinically meaningful improvements in cognitive, attention, and language scores. The present study aims to assess the effect of a similar nutritional intervention on brain development and subsequent neurodevelopmental outcome in infants born very and extremely preterm. Methods This is a randomized, placebo-controlled, double-blinded, parallel-group, multi-center trial. A total of 130 infants, born at less than 30 weeks of gestation, will be randomized to receive a test or control product between term-equivalent age and 12 months corrected age (CA). The test product is a nutrient blend containing DHA, choline, and UMP amongst others. The control product contains only fractions of the active components. Both products are isocaloric powder supplements which can be added to milk and solid feeds. The primary outcome parameter is white matter integrity at three months CA, assessed using diffusion-tensor imaging (DTI) on MRI scanning. Secondary outcome parameters include volumetric brain development, cortical thickness, cortical folding, the metabolic and biochemical status of the brain, and product safety. Additionally, language, cognitive, motor, and behavioral development will be assessed at 12 and 24 months CA, using the Bayley Scales of Infant Development III and digital questionnaires (Dutch version of the Communicative Development Inventories (N-CDI), Ages and Stages Questionnaire 4 (ASQ-4), and Parent Report of Children's Abilities - Revised (PARCA-R)). Discussion The investigated nutritional intervention is hypothesized to promote brain development and subsequent neurodevelopmental outcome in preterm born infants who have an inherent risk of developmental delay. Moreover, this innovative study may give rise to new treatment possibilities and improvements in routine clinical care. Trial registration WHO International Clinical Trials Registry: NL-OMON56181 (registration assigned October 28, 2021).